Structural Design and Kinematics Analysis of a Uncoupled Translational Parallel Robotic Mechanism - Xi Mao; Yanbin Zhang; Yifu Zhao (Jixie chuandong)
An uncoupled spatial translational parallel robotic mechanism with three degrees of freedom (DOF) is presented, which is composed of a moving platform connected to a fixed platform by three identical kinematic chains. Based on the screw theory, the kinematic output characteristic of the mechanism is analyzed. The analytical expressions of position, velocity and acceleration are derived. The form of Jacobian matrix is 3×3 diagonal, so it reveals that the inputs of the actuated joints and outputs of the moving platform satisfy one-to-one corresponding relationship, respectively. Then, the kinematic simulation of this parallel mechanism is carried out by Matlab and SolidWorks software, and the position, velocity and acceleration curves are described as well. The simulation results show that the theoretical analysis is correct. Finally, singularity and its workspace are discussed respectively.